HOMAGE – Modes of housing and development in older age - (:unkn) unknown (My University, 2025)
"Homage" examines modes of housing of older persons in the Canton of Neuchâtel. Rather than examining the person in isolation, this project assumes that the development of older persons depends on both their past trajectory, and the overall configuration of the social and material arrengments of their situated daily life. The project aims identifying the conditions in which various modes of housing may support older person's autonomous and meaningful life. The project is designed as collaborative, and thus has both fundamental goals (i.e., to contribute to our understanding of learning and development in old age) and a more applied goal (i.e., to contribute to the evolution of the living arrangements for older persons).
Keywords: Développement; logement; personne âgée; Neuchâtel